Reconciling Stability and Growth : Smart Pacts and Structural Reforms - Beetsma, Roel (IMF Working Papers; Working Paper ;, 2003)
This paper analyzes the decision of a government facing electoral uncertainty to implement structural reforms in the presence of fiscal restraints similar to the Stability and Growth Pact. The model shows that a pact may harm structural reforms, sacrificing future growth for present stability. The welfare gains brought about by a pact depend on a trade-off between the reduction in the deficit bias and the induced reduction in the amount of structural reform. A pact becomes more attractive ('smarter') if it takes into account the fiscal impact of structural reforms, in line with a recent proposal by the European Commission.